Mothers and their teenage daughters\' perspectives on the relationship between them - Tayebe Ziaei; Maryam Ghanbari Gorji; Naser Behnampour; Masumeh Rezai (Golestan University of Medical Sciences, 2018)
Background: Adolescence is a very troublesome period involving many physical, sexual and psychological changes. Therefore, researchers naintain that adolescents need to make a good relationship with their parents and particually their mothers to adapt to the changes at this age and be compatible with them. Hence, this study aimed to determine the mothers and their teenage daughters'perspectives on the relationship between them.   Methods: This cross-sectional study was conducted on 168 mothers and 13-15 year-old daughters who were provided with health services by health centers in Gorgan.  The samples were selected randomly and had the inclusion criteria. Data were collected through a valid and reliable questionnaire of "general discussion between mother and daughter" . Data were also analyzed using Chi-square and independent t-test at a significant level of 0.05 by  SPSS 16.   Results: The mean score of general conversation between mother and daughter was 55.95 (74-38) from the mothers' perspective, and 52.30 (76-25) from the daughters' viewpoint. The difference between the two perspectives was significant (p-value<0.001). In addition, no significant difference was observed between the mothers and daughters' perspectives on the number of communications with daughters, the feeling of closness to parents, and the responsibility to educate them.   Conclusion:The difference in the scores assigned to the general discussion between mother and daughter of their perspectives indicates the need for interventions aiming at increasing their communication skills to maintain and improve the girls' health.